The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00213-018-4973-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of NAD-299 and TCB-2 on learning and memory, hippocampal BDNF levels and amyloid plaques in Streptozotocin-induced memory deficits in male rats

Abstract: These findings suggest that 5-HT1AR blockade by NAD-299 and 5-HT2AR activation by TCB-2 improve cognitive dysfunction in icv-STZ-treated rats, and these drugs may potentially prevent the progression of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 81 publications
0
26
0
1
Order By: Relevance
“…Here, we showed that acute nicotine enhanced 5-HT 2A R-IR neurons of the DG, this might contribute to nicotine-enhanced hippocampal-dependent learning [56] considering 5-HT 2A R participates significantly to the well-documented contribution of 5-HT to memory [57,58]. TCB-2, indeed, can improve cognitive dysfunction [59] and enhance hippocampal and amygdala-dependent memory [60]. The increased expression of 5-HT 2A Rs in the neuropil of mPFC and VTA might contribute to nicotine-induced enhanced cognition [61] and positive reinforcement [18].…”
Section: Discussionmentioning
confidence: 66%
“…Here, we showed that acute nicotine enhanced 5-HT 2A R-IR neurons of the DG, this might contribute to nicotine-enhanced hippocampal-dependent learning [56] considering 5-HT 2A R participates significantly to the well-documented contribution of 5-HT to memory [57,58]. TCB-2, indeed, can improve cognitive dysfunction [59] and enhance hippocampal and amygdala-dependent memory [60]. The increased expression of 5-HT 2A Rs in the neuropil of mPFC and VTA might contribute to nicotine-induced enhanced cognition [61] and positive reinforcement [18].…”
Section: Discussionmentioning
confidence: 66%
“…For example, activating 5-hydroxytryptophan 1A (5-HT1A) or 5-HT2A receptors that induce hippocampal BDNF expression has been examined. Afshar et al investigated the effects of NAD-299 (an antagonist for 5-HT1A receptor) and TCB-2 (an agonist for 5-HT2A receptor) on learning and memory function in streptozotocin (STZ)-induced memory deficit animal models [ 17 ]. In their study, rats received intracerebroventricular (icv) injection of STZ exhibited decreased discrimination index in the novel object recognition test, reduced BDNF, and increased Aβ plaques in the brain, which were reversed by treatment with NAD-299 or TCB-2 [ 17 ].…”
Section: Activation Of Bdnf/trkb System By Compoundsmentioning
confidence: 99%
“…Afshar et al investigated the effects of NAD-299 (an antagonist for 5-HT1A receptor) and TCB-2 (an agonist for 5-HT2A receptor) on learning and memory function in streptozotocin (STZ)-induced memory deficit animal models [ 17 ]. In their study, rats received intracerebroventricular (icv) injection of STZ exhibited decreased discrimination index in the novel object recognition test, reduced BDNF, and increased Aβ plaques in the brain, which were reversed by treatment with NAD-299 or TCB-2 [ 17 ]. Influence of neuropeptide Y (NPY), which is implicated as potential therapeutic target of HD, in expression of BDNF has been reported [ 18 ].…”
Section: Activation Of Bdnf/trkb System By Compoundsmentioning
confidence: 99%
“…For histological study, the brains of anesthetized rats from the electrophysiology test were fixed through perfusion with a paraformaldehyde solution. The brains were dehydrated, embedded in paraffin, and sliced into a series of coronal sections of 5 μm thickness according to previous studies [47,53].Then, sections were used for TdT-mediated dUTP end labeling (TUNEL) staining, in which DNA fragmentation and apoptosis were detected by a TUNEL Detection Kit (Abcam) following the manufacturer's instructions. After staining, the sections were analyzed under a light microscope (× 400, Olympus).…”
Section: Apoptosis (Tunel Assay)mentioning
confidence: 99%